Posamezniki v postopku ničnostne tožbe pred Sodiščem EU - Grah, Ines (Podjetje in delo, 2016)
Conditions for natural and legal persons that filed an action for annulment before the Court of Justice of the European Union were considered particularly strict and limited their access to justice. The author discusses changes brought by the Treaty of Lisbon in Article 263(4) of the Treaty of the Functioning of the European Union. At first, she introduces types of reviewable acts in the EU and conditions of direct and individual concern. After the description of changes in the Treaty of Lisbon that consider classification of EU acts, she presents and assesses the latest case law of the Court of Justice of the European Union that defines the term "regulatory act which does not entail implementing measures". Finally, after taking into account other changes in the Treaty of Lisbon, she reveals her view on the improvement of possibilities for individuals to bring action for annulment to the Court of Justice of the European Union.
Keywords: Evropska unija; fizične osebe; pravne osebe; pravno varstvo; sodišča; sodni postopek